UMPSA and Malaysian Prisons Department strengthen collaborative partnership - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
PEKAN, 4 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and the Malaysian Prisons Department (JPM) have recently strengthened their collaborative ties in advancing the TVET Agenda.